Comparative study of ring yarn properties spun with static and rotary grooved contact surfaces. Issue 16 (August 2018) - Yu, Hao; Liu, Keshuai; Jun, Chen; Fu, Chiyu; Xia, Zhigang; Xu, Weilin
Spinning with a static contact surface is an energy-saving method to reduce spun yarn hairiness; however, the spun yarn irregularity and tensile properties are deteriorated. To prohibit the deteriorations, this paper introduces a rotary grooved surface contacting ring spinning strand within the yarn formation zone. In theory, the modeling analysis of spinning with contact surface is conducted to reveal the prohibition mechanism of yarn irregularity and tensile property deteriorations for a rotary grooved surface. Theoretical analysis results indicated that groove-yarn surface friction could wrap the concentrated hairs onto yarn stem while block inflowing twists to the spinning strangle zone; the rotary grooved surface could reduce twist blockage and hair wrapping concentrations to better the situation after a comparison with the static grooved surface. Then, two kinds of specially-designed grooved cylinders (one was rotatable while the other was static) were used to validate the theoretical analysis. The experimental results showed that, unlike the static grooved cylinder which significantly deteriorated the original yarn unevenness CVm, the rotary achieved significant hairiness reduction without any significant deterioration of other yarn properties. This might be due to the decreased friction and twist propagation for the rotary grooved cylinder contacting the spinning strand. In this case, spinning with a rotary grooved cylinder was preferably applied in the first step to control ring spun yarn hairiness.